Islam Melayu komunis : wawancara dengan Abdullah C.D., Rashid Maidin, Abu Samah. - Strategic Info Research Development (Petaling Jaya, Malaysia : SIRD, 2005)
Account of Abdullah C.D., Rashid Maidin, and Abu Samah, Malaysian Muslim communists and political activists joining the Malayan Communist Party; interviews.
In Malay.
Keywords: Abdullah C. D. -- 1923-; Rashid Maidin, -- 1917-; Abu Samah bin Muhamad Kasim, -- 1926-; Malayan Communist Party -- History; Communists -- Malaya -- Biography; Political activists -- Malaya -- Biography